Creation of Beauty - Zhong, Cuixiang (European Journal of Applied Sciences, 2021)
Human beings have never stopped pursuing and worshiping beauty, but so far they have not found the secret to produce beautiful offspring. Some beautiful couples may not have beautiful children, but some ordinary looking couples can have beautiful children. These common problems in life make many parents puzzled. Therefore, according to the growth and development process of his daughter, the author found the general law of giving birth to beauty, that is, to make a couple have beautiful children, the woman’s body should not be much smaller than the man's, or the woman should be plump or fat enough to have enough skin and meat to package the man's skeleton; If the man's back is straight, the child also has a straight body. If people follow this rule, they can greatly increase the proportion of beauties and make the world much more beautiful.